Pengaruh Samsat Keliling, Sosialisasi Perpajakan dan Sanksi Pajak Terhadap Kepatuhan Pajak Kendaraan Bermotor Kabupaten Ponorogo - Ardyan Firdausi Mustoffa; Titin Eka Ardiana; Andra Eka Vebriana (ITB AAS INDONESIA, 2022)
In Ponorogo there are still units of motorcycle that are in arrears so that tax compliance is not optimal. This study aims to determine the effect of the implementation of Samsat keliling service, taxation socialization, and tax penalties on taxpayer compliance of motorcycle. This research belongs to the type of quantitative research with primary data originating from the distribution of questionnaires. This study uses a probability sampling technique with a total of 100 respondents spread over Samsat keliling Sambit and Jenangan. The results showed that: (1) Samsat keliling service had a positive and significant effect on the tax compliance of motorcycle, (2) tax socialization had a positive and significant effect on the tax compliance of motorcycle, (3) tax penalties had a positive and significant effect on the tax compliance of motorcycle, (4) Samsat keliling service, tax socialization, and tax penalties simultaneously have a positive and significant effect on the tax compliance of motorcycle.